Assessment of glutamate in striatal subregions in obsessive-compulsive disorder with proton magnetic resonance spectroscopy. Issue 1 (30th April 2015) - Simpson, Helen Blair; Kegeles, Lawrence S.; Hunter, Liane; Mao, Xiangling; Van Meter, Page; Xu, Xiaoyan; Kimeldorf, Marcia B.; Pearlstein, Sarah L.; Slifstein, Mark; Shungu, Dikoma C.
Abstract: Glutamatergic signaling abnormalities in cortico-striatal circuits are hypothesized to lead to the repetitive thoughts and behaviors of obsessive-compulsive disorder (OCD). To test this hypothesis, studies have used proton magnetic resonance spectroscopy ( 1 H MRS) to measure glutamatergic compounds in the striatum of individuals with OCD. However, no studies have used methods that could measure glutamate minimally contaminated by glutamine and γ-aminobutyric acid (GABA) in striatal subregions. Therefore, in this study, a proton MRS imaging ( 1 H MRSI) technique with relatively high spatial resolution at 3.0 T was used to measure minimally contaminated glutamate levels in three striatal subregions (i.e., dorsal caudate, dorsal putamen, and ventral striatum) in 15 unmedicated adults with OCD and 16 matched healthy control subjects. No significant group differences in glutamate levels were found in any of the three striatal subregions. In contrast, a study in unmedicated pediatric OCD patients that measured glutamatergic compounds in the dorsal caudate by MRS at 1.5 T found significant elevations. Further studies are warranted to assess whether these discrepant MRS findings are due to differences in subject age or MRS methodology, or potentially are associated with glutamatergic gene variants implicated in OCD. Highlights: Tested the glutamatergic hypothesis for OCD. Recruited unmedicated adults with OCD (most were treatment-naïve). Used an imaging method to measure relatively uncontaminated glutamate. Found no glutamatergic abnormalities in the caudate or other striatal subregions.